2007
DOI: 10.1108/09544780710720826
|View full text |Cite
|
Sign up to set email alerts
|

The role of control charts in promoting organisational learning

Abstract: Purpose -The purpose of this paper is to examine the theoretical interface between statistical thinking, the statistical method of the control chart, and contemporary theories of organisational learning in regard to processes and their improvement. Design/methodology/approach -Theoretical discussion results in an integrated model showing how statistical thinking and methods relate to organisational learning. This is supported by findings from a food industry research project following a design of: exploration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 29 publications
2
25
0
7
Order By: Relevance
“…The authors also emphasize the importance of management aspects such as senior management support and of technical aspects, such as training for CI implementation and maintenance. Despite the fact that SPC is considered a CI form (Mason & Antony, 2000;Grigg & Walls, 2007b), few studies have analyzed the CSF related to SPC use in Brazilian companies.…”
Section: Identifying Csf For Spc Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also emphasize the importance of management aspects such as senior management support and of technical aspects, such as training for CI implementation and maintenance. Despite the fact that SPC is considered a CI form (Mason & Antony, 2000;Grigg & Walls, 2007b), few studies have analyzed the CSF related to SPC use in Brazilian companies.…”
Section: Identifying Csf For Spc Implementationmentioning
confidence: 99%
“…The most cited CSFs in the literature (80% of the 173 citations about CSF) are shown in Table 1. (1) Gordon et al (1994), (2) Does et al (1997), (3) Rungtusanatham et al (1999), (4) Xie & Goh (1999), (5) Mason & Antony (2000), (6) Antony et al (2000), (7) Rungasamy et al (2002), (8) Antony & Taner (2003), (9) Grigg & Walls (2007a), (10) Grigg & Walls (2007b), (11) Chen et al (2008), (12) Elg et al (2008), (13) Putri & Yusof (2008), (14) Phyanthamilkumaran & Fernando (2008), (15) Rohani et al (2009), (16) Rohani et al (2010), (17) Mahanti & Evans (2012), (18) Rantamaki et al (2013), (19) Sharma & Kharub (2014), (20) Lim et al (2014).…”
Section: Identifying Csf For Spc Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach is the normality of the control limits, where 2 out of 3 consecutive points are outside the limits of 2σ [8]. The food industry use control charts in different ways depending upon their level of maturity in statistical thinking [15]. In a survey conducted in UK food industry, revealed that while there are large differences in process types, quality priorities and key measures among different sub-sectors of the industry, the use of control charts was broadly similar.…”
Section: Control Chartmentioning
confidence: 99%
“…In a survey conducted in UK food industry, revealed that while there are large differences in process types, quality priorities and key measures among different sub-sectors of the industry, the use of control charts was broadly similar. This generally extended to the use of control charts for recording or monitoring product net weight and volume data [15].…”
Section: Control Chartmentioning
confidence: 99%